Malaysian Communication And Multimedia Commission's (Mcmc) Law Enforcement Spectrum: Exploring Arrest Authority - Mimi Sofiah Ahmad Mustafa; Yuhanza Othman; Nasihah Naimat; Ida Rahayu Mahat; Marziana Abd Malib; Mohd Ab Malek Md Shah; Muhammad Arif Haron (Universiti Sains Islam Malaysia, 2025)
The Malaysian Communications and Multimedia Commission (MCMC) regulates multimedia and communication activities and plays a role in protecting consumers from harms such as online scams and digital fraud. However, it is rather ironic that the unit mandated to receive public complaints about scams does not have the power to make an arrest upon the presentation of sufficient proof, a task that often rests with the Royal Malaysian Police Department (RMPD). Therefore, this study examines a key enforcement gap in the Malaysian Communications and Multimedia Commission’s (MCMC) role, specifically its lack of arrest powers when handling scam-related complaints. It highlights the challenges this limitation poses and proposes the inclusion of arrest authority to strengthen MCMC’s enforcement effectiveness. In doing so, this study employed a qualitative research method in which data were collected through semi-structured interviews conducted with officers from the MCMC, the RMPD, and the Ministry of Communications and Multimedia. Secondary data were gathered from internet sources, relevant legislations, and journals to illustrate the law in this area. Upon analysing the primary and secondary data, the researchers found that it is imperative to grant arrest power to the MCMC due to the challenges encountered in carrying out its tasks. The outcomes of this study can facilitate the Parliament in passing a law to confer the power of arrest to the MCMC through the current legislation, thus reducing the burden of the RMPD in making arrests related to media and communication cases. The public directly benefits from this study as it raises their confidence to lodge complaints with the MCMC, knowing fully well that the commission possesses the power to make an immediate arrest.